Analysis of Optimization of Village Fund Allocation for Community Empowerment in The Economic Sector - Hafidz Noor; Rahmat Rahmat; Dwi Iman Muthaqin (Jurnal Civicus, 2022)
The allocation of village funds can be said to be optimally empowering the community if it is channeled to the community to prosper and strengthen the economy as part of the economy civics of the community if it is in accordance with a careful planning process and is also based on applicable laws and regulations. Community welfare can be seen when there is an increasing change of opinion accompanied by qualified skills and knowledge so that it can reduce the level of poverty. This research is intended to be able to identify and inform the extent to which the allocation of village funds is optimally distributed to the community or not, especially in the jurisdictional area of Bojongsari Village. This research in the process of preparation using a qualitative approach with a descriptive study method. The data collection technique that the researcher uses is by using interviews, observation, documentation studies, and literature studies. The results of the research obtained on field objectivity show that the impact felt by the community from the empowerment program using village funds has been felt, but if overall the village funds are said to have not been optimally allocated because they are not in accordance with the laws and regulations that govern it.